Pengaruh Pembelajaran Project Based Learning (PjBL) berbasis STEAM terhadap Kemampuan Kognitif Anak - Adela Tsamrotul Fikriyah; Hibana Hibana; Bela Mayang Sari (Jurnal PG-PAUD, 2024)
Children in preschool who are five or six years old and preparing to start primary school are under pressure to have good reading, writing, and math skills, which forces them to pick things up quickly. Due to cognitive skill delays, children require engaging media that adheres to both the Pancasila student profile and the autonomous curriculum. For example, STEAM-based PjBL can be used to enhance the academic abilities of children between the ages of five and six. The study approach employs a quantitative experimental design to ascertain whether variable X has an impact on variable Y. Children's cognitive capacities as variable (Y) and STEAM-based project-based learning (PjBL) as variable X. The 40-student An-Nur 2 Kindergarten serves as the research site. Because random sampling is used in the sampling technique, every member of the population has the chance to be included in the sample, which is picked at random. An observation form on the cognitive capacities of children aged 5 to 6 is used as a research tool. In this study, t-tests, homogeneity, and normality tests were used in the data analysis process. According to research findings, children's cognitive abilities are significantly impacted by STEAM-based Project Based Learning (PjBL). Before going to the elementary school level, STEAM-based PjBL learning activities can serve as a stimulus for kids to work through issues and challenges in learning calistung. Since children's cognitive abilities influence the STEAM system by 60%, it is deemed to be fairly effective for use with children between the ages of 5 and 6 based on the N-Gain score criteria.